The effect of partial substitution of wheat flour with quinoa flour on the processing properties of bakery products (Damascus University Journal of agriculture sciences, 2025)
This research was carried out at the Department of Food Science, Faculty of Agriculture, Damascus University, with the aim of evaluating the quality characteristics of pan bread and biscuits prepared from high-quality wheat flour and partially substituted with different proportions of whole quinoa seed flour. The chemical composition analysis of pan bread and biscuits showed a significant effect of adding quinoa flour on all the studied chemical indicators, and therefore these results reflected the health benefits of using quinoa flour in food applications and for the development of health-promoting bakery products as innovative products. On the other hand, the addition of quinoa flour led to a significant decrease in loaf volume by (10.29%) when replacing 40% of wheat flour with quinoa flour, and this was also accompanied by a decrease in the values of the specific volume of bread. Similarly, the spread ratio of biscuits was decreased. These results indicated that using quinoa flour to replace wheat flour had advantages in producing biscuits from weak wheat vatieties in order to improve the texture of the resulting biscuits, and in producing desirable biscuits with low spread ratios. However, the results of this research contradicted the results of previous studies, which showed an increase in the biscuit hardness values with a high percentage of replacing wheat flour with quinoa flour in the mixture. In addition, there were no significant differences between the sensory evaluation scores for bread and biscuits made from only wheat flour and the quinoa flour mixture up to 10%, as the significant differences started to appear when the percentage of replacement with quinoa flour was increased up to 20%. Pan bread supplemented with a higher-level substitution of quinoa flour showed a more brownish crust than the control bread. In general, bread and biscuits supplemented with quinoa flour showed moderate similarity with general acceptance of panelists, indicating the acceptability of pan bread and biscuits developed with quinoa flour by up to 40%.
Keywords: high quality flour; quinoa flour; chemical properties; processing properties; sensory properties; spread ratio; specific weight